Carbon Pricing in Japan - Arimura, Toshi H.; Matsumoto, Shigeru; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This open access book evaluates, from an economic perspective, various measures introduced in Japan to prevent climate change. Although various countries have implemented such policies in response to the pressing issue of climate change, the effectiveness of those programs has not been sufficiently compared. In particular, policy evaluations in the Asian region are far behind those in North America and Europe due to data limitations and political reasons. The first part of the book summarizes measures in different sectors in Japan to prevent climate change, such as emissions trading and carbon tax, and assesses their impact. The second part shows how those policies have changed the behavior of firms and households. In addition, it presents macro-economic simulations that consider the potential of renewable energy. Lastly, based on these comprehensive assessments, it compares the effectiveness of measures to prevent climate change in Japan and Western countries. Providing valuable insights, this book will appeal to both academic researchers and policymakers seeking cost-effective measures against climate change. .
Expectations for Carbon Pricing in Japan in the Global Climate Policy Context -- Climate policy in the commercial sector: A survey of commercial buildings in Japan -- Climate Policy in Household Sector -- Climate Policy in Transportation Sector: Role of Carbon Pricing.
Keywords: Power resources; Energy policy; Energy and state; Cogeneration of electric power and heat; Fossil fuels; Natural Resource and Energy Economics; Energy Policy, Economics and Management; Fossil Fuel